The dead of night - Lerangis, Peter (39 clues. Cahills vs. Vespers ;, 2012)
"The Vespers have crossed a line. Amy and Dan were devastated when the Vespers kidnapped seven Cahills around the world, holding them hostage until Amy and Dan delivered an impossible ransom. But at least the hostages were Cahills - members of the world's most powerful family, trained to face all odds. Now the Vespers have gone too far. They've kidnapped Atticus, an innocent 11 year old boy and Dan's only friend. Now Dan and Amy are in the struggle of their lives. Because if they can't outwit the Vespers, the unthinkable will happen . . . Atticus will die."--Amazon.com.